Economic design of product and process parameters under the specified process capability value. Issue 6 (2nd November 2018) - Chen, Chung-Ho; Chou, Chao-Yu
Abstract: In this paper, the author presents a jointly design model with manufacturing quantity, specification limits, process mean and the parameters of X -bar control chart based on the specified process capability index value. The quality loss of a product is set to be related to the limits of the control chart. Assume that the quality characteristic of a product is normally distributed with known standard deviation and adjustable mean. The production process may have a shift in the process mean, while the process standard deviation remains constant. The optimal combination of parameters is determined by minimizing the expected total cost of product under the specified value. This integrated model is a generalization of the economic manufacturing quantity (EMQ) model with statistical quality control chart. Finally, the numerical example and sensitivity analysis of parameters will be provided for illustration.